RECONSIDERING NAFAQAH OF FAMILY RESILIENCE DURING THE COVID-19 PANDEMIC IN ISLAMIC LEGAL PERSPECTIVE - Nurdin, Ridwan; Ridwansyah, Muhammad; Iskandar, Zakyyah (State Islamic University North Sumatra, 2021)
Abstract: The main goal of this research is to comprehend deeply the relation between husband and wife relating to the responsibilty of nafaqat in their family. The methodology used is juridical-sociological; where the data analyzed from textual livelihood obligations conditional or current contextual forces that all family members also have a responsible role in terms of living. The results of the study are as follows: that al-Baqarah requires a husband to provide a living to his wife, but in another context, a wife or other family members can play a role in maintaining family resilience during the Covid-19 pandemic resistance. In reality, however, the nafaqat become mutual responsibility of the husband and wife without any objection. Keywords: nafaqat, family resilience, Covid-19 pandemic